Analysis of the Internal Control System for Receivables at CV. Putra Riau Mandiri - Hutabarat, Lister Eveline (Luxury: Landscape of Business Administration, 2024)
In carrying out its activities to achieve the stated goals, companies must exercise control. The controls implemented must provide benefits, in this case being able to increase the effectiveness and efficiency of operations. This research focuses on analysis of the receivables control system. The purpose of this research is to describe and analyze how internal control at CV. Putra Riau Mandiri Pekanbaru. This research uses qualitative tests with a descriptive-analysis approach to internal control of trade receivables which refers to the COSO framework on the elements of internal control. The results of the research show that in the transaction authorization section the separation of duties is still not in accordance with COSO theory because there are still trapped functions and responsibilities in the sales and billing sections. Then, adequate documents are in accordance with COSO theory that every transaction has been properly documented. However, in the internal information section between the billing, accounting and finance sections, there is still a need for internal documents, namely payment receipt documents in hardfile and softfile form. Then, in terms of data and file security, it is running in accordance with COSO theory because the existing data has been properly backed up. The cause of uncollected receivables due to the manager's ignorance regarding several invoices is because there are duplicate tasks in the billing department, then there are frequent delays in recording the repayment of receivables so that in recapitulation of repayment there are often errors in recording receivable payments.